Implementation and Impact of a Hospital-Wide Instrument Set Review: Early Experiences at a Multisite Tertiary Care Academic Institution. (January 2019) - Yoon, Seungwon; Zygourakis, Corinna C.; Seaman, Joshua; Zhu, Min; Ahmed, A. Karim; Kliot, Tamara; Antrum, Sheila; Goldberg, Andrew N.
A multidisciplinary team of nurses, sterile processing technicians, and surgeons reviewed 609 otolaryngology–head and neck surgery (OHNS) surgical instrument sets at the study institution's 3 hospitals. Implementation of the 4-phase instrument review resulted in decreased OHNS surgical instrument set types from 261 to 234 sets, and a decreased number of instruments in these sets from 18 952 to 17 084. The instrument set review resulted in an estimated savings of 35 665 in sterile processing costs for the OHNS department. Instrument review applied to all 10 surgical specialties at the institution would result in an estimated annual savings of 425 378. Through effective leadership, multidisciplinary participation of all key stakeholders, and a systematic approach, this study demonstrates that a hospital-wide quality improvement intervention for instrument set optimization can be successfully performed in a large, multisite tertiary care academic hospital.